REFLECTIVE MODUL BERBASIS CHILD FRIENDLY SCHOOL UNTUK MENINGKATKAN KEMAMPUAN LITERASI DAN KARAKTER SISWA - Santy Dinar Permata; Ali Mustadi (Kwangsan: Jurnal Teknologi Pendidikan, 2020)
Welcoming the Golden Generation 2045 program the Indonesian government envisions the literacy movement in schools as an effort to improve the literacy abilities and character of students. The problem in the field is the lack of types of student reading that are able to develop students 'thinking power and character, therefore this study aims to produce reflective module development products based on child friendly schools that are fit for use by fifth grade elementary school students in school literacy activities as a means of increasing students' literacy abilities and character. The type of research used is Research and Development (RnD) research, referring to the type of research developed by Borg and Gall. The subjects of the study were the fifth grade 73 students at SDN Tegalrejo 3 and SDN Bangirejo 1. Collecting data through interviews, observations, questionnaires and response scales. The analysis technique used is descriptive analysis. The results showed that the child friendly school-based reflective module products met the eligibility criteria by referring to the results of the questionnaire validation by media experts and material experts as well as the scale of responses of teachers and fifth grade elementary school students. AbstrakMenyongsong program Generasi Emas 2045 pemerintah Indonesia mencangangkan adanya gerakan literasi di sekolah sebagai upaya untuk meningkatkan kemampuan dan karakter siswa. Permasalahan dilapangan adalah kurangnya jenis bacaan siswa yang mampu mengembangkan daya pikir dan karakter siswa oleh karena itu penelitian ini bertujuan untuk menghasilkan produk pengembangan reflective modul berbasis child friendly school yang layak digunakan oleh siswa kelas V SD dalam kegiatan literasi sekolah sebagai sarana meningkatkan kemampuan literasi dan karakter siswa. Jenis penelitian yang digunakan adalah penelitian Research and Development (RnD) mengacu pada jenis penelitian yang dikembangkan oleh Borg and Gall. Subjek penelitian adalah 73 siswa kelas V SD di SDN Tegalrejo 3 dan SDN Bangirejo 1. Pengumpulan data melalui wawancara,observasi,angket dan skala respon. Teknik analisis yang digunakan adalah analisis deskriptif. Hasil penelitian menunjukkan bahwa produk reflective modul berbasis child friendly school memenuhi kriteria kelayakan dengan mengacu pada hasil validasi angket oleh ahli media dan ahli materi serta skala respon guru dan siswa kelas V SD.